2007
DOI: 10.2202/1542-0485.1149
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Collective Reputation for Environmentally-Friendly Production Methods: The Case of Val di Gresta

Abstract: In this paper we investigate consumers' preferences for various environment-friendly production systems for carrots. We use discrete-choice multi-attribute stated-preference data to explore the effect of collective reputations from growers of an Alpine valley known for its environmentfriendly production: Val di Gresta 'the valley of organic orchards'. Data analysis of the panel of discrete responses identifies unobserved taste heterogeneity for organic, bio-dynamic and place of origin, while observed heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…While several studies investigated the price premium that consumers were willing to pay for organic food, most of these studies either used a single organic logo or the word 'organic' to distinguish organic from conventional products (see e.g. Hoogland, de Boer, & Boersema, 2007;Napolitano et al, 2010;Scarpa & Thiene, 2007). A study of consumer preferences in the United States found that consumers were willing to pay a higher price premium for the USDA organic logo than for a generic organic label (Van Loo, Caputo, Nayga, Meullenet, & Ricke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies investigated the price premium that consumers were willing to pay for organic food, most of these studies either used a single organic logo or the word 'organic' to distinguish organic from conventional products (see e.g. Hoogland, de Boer, & Boersema, 2007;Napolitano et al, 2010;Scarpa & Thiene, 2007). A study of consumer preferences in the United States found that consumers were willing to pay a higher price premium for the USDA organic logo than for a generic organic label (Van Loo, Caputo, Nayga, Meullenet, & Ricke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have analysed consumers' preferences for the organic method of production and the origin of production attributes (Loureiro and Hine, 2002;Scarpa et al, 2005Scarpa et al, , 2007Hustvedt and Bernard, 2008;Hu et al, 2009Hu et al, , 2012James et al, 2009;Yue and Tong, 2009;Pouta et al, 2010;Costanigro et al, 2011;Onken et al, 2011;Onozaka and McFadden, 2011;Aprile et al, 2012;Moser and Raffaelli, 2012;Gracia et al, 2013). The results of these studies suggest that while consumers positively value the organic label and the origin of production, there are mixed results regarding which of these two attributes is valued more by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…This finding differs from the ones by Loureiro & Hine (2002) and Pouta et al (2010) who found that consumers' WTP for the origin of production was higher than for the method of production for USA and Finnish consumers and for potatoes and poultry, respectively. However, there is substantial evidence that the importance of the method of production and origin of production depends on the consumer segment and on the analyzed products (Scarpa et al, 2005(Scarpa et al, , 2007aHu et al, 2009;James et al, 2009;Yue & Tong, 2009;Wolf et al, 2011). Our results reinforce the notion that the relative importance attached by consumers to the method and origin of production attributes when shopping depends on the specific product.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several empirical papers analyzed preferences for both attributes, method of production and origin of production (Loureiro & Hine, 2002;Scarpa et al, 2005Scarpa et al, , 2007aHu et al, 2009;James et al, 2009;Yue & Tong, 2009;Pouta et al, 2010;Wolf et al, 2011;Hu et al, 2012) using different levels for both attributes 6 . These studies used a choice experiment to assess consumers' willingness to pay (WTP) for different products (potatoes, oranges, grapes, olive oil, poultry, tomatoes, carrots, applesauce, blueberry products and milk) in USA and Europe (Finland and Italy).…”
mentioning
confidence: 99%